2020
DOI: 10.29333/ejgm/7885
|View full text |Cite
|
Sign up to set email alerts
|

Association between Lifestyle and Severity of Menopausal Symptoms in Postmenopausal Women

Abstract: Menopause is a physiological occurrence characterized by a series of bothersome symptoms. Given that lifestyle affects people's health in general and many menopausal symptoms are influenced by changes in lifestyle, this study aimed to determine the relationship between lifestyle and severity of menopausal symptoms in women referred to health centers in Yazd city. Method: This cross-sectional study was performed using stratified random sampling where 343 postmenopausal women who had experienced natural menopaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…About 44.2 percent of them reported moderate vaginal dryness. This finding agreed with Yoshany et al (2020), whose results displayed that over a third of women experienced severe urogenital symptoms, and also with the study of Misiker, Kashala, and Misker (2023), who reported that the most severe menopausal symptom was the sexual problem. The current study mentioned that the mean total menopausal rating score was 16.85±3.56.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…About 44.2 percent of them reported moderate vaginal dryness. This finding agreed with Yoshany et al (2020), whose results displayed that over a third of women experienced severe urogenital symptoms, and also with the study of Misiker, Kashala, and Misker (2023), who reported that the most severe menopausal symptom was the sexual problem. The current study mentioned that the mean total menopausal rating score was 16.85±3.56.…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to the difficult socioeconomic conditions that the country is going through as a result of the global economic crisis nowadays. Identical results appeared in the study of Yoshany et al (2020). While this result is opposed to Abo- Ali and Oka (2021), where the investigated women's health-promoting lifestyle profile average score was moderate (120.38±16.63), This disagreement may be due to differences in the cultures and attitudes of the participating women in different societies.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, it was also found that most respondents worked, with most working as civil servants. This is different from the research by Mazloomy Mahmoodabad et al in Iran, where the majority of their respondents are housewives (14). More working respondents experienced menopausal symptoms in this study compared to non-working respondents.…”
Section: Characteristicscontrasting
confidence: 99%
“…[4]. A study by Yoshany et al showed a relationship between severity of menopausal symptoms and lifestyle factors [5]. Most women experience specific or nonspecific symptoms of menopause that significantly affect their quality of life, notably by increasing the risk of obesity, osteoporosis, met abolic syndrome, and cardiovascular disease [6].…”
Section: Introductionmentioning
confidence: 99%